Actinomycosis in concha bullosa: a case report - Kenar, Fethullah; Ulu, Şahin; Dilek, Hüsniye; Ayçiçek, Abdullah; Yıldız, Hüseyin (ENT Updates, 2014)
Actinomyces, a gram-positive, anaerobic-to-microaerophilic species of bacteria, lives as commensal in human body. In this report, actinomycosis in concha bullosa in a 51-year-old woman is presented and it is aimed to add a case to the very rarely reported atypical locations of actinomycosis. Also, diagnostic and therapeutic approaches were discussed. Actinomycosis should also be considered in the differential diagnosis of the patients with effluent at head and neck region and nasal cavity in daily practice of otorhinolaryngology.